Effects of black carrot concentrate on some physicochemical, textural, bioactive, aroma and sensory properties of sucuk, a traditional Turkish dry-fermented sausage - Ekici, Lutfiye; Ozturk, Ismet; Karaman, Safa; Caliskan, Oznur; Tornuk, Fatih; Sagdic, Osman; Yetim, Hasan (ELSEVIER, 2015)
In this study, Turkish fermented sucuk samples were produced by incorporating of 0.5, 1 and 2 g/100 g black carrot concentrate (BCC) in the presence/absence of sodium nitrite and effects of BCC on some physicochemical, microbiological, bioactive, aroma, textural and sensory properties of sucuk were investigated after fermentation for 12 days. The highest total phenolic content value was determined in sucuk sample added with 2 g/100 g BCC and no nitrite and antiradical activities of the sucuk samples were significantly affected from addition of BCC. Incorporation of BCC did not show significant effect on the hardness values, while it improved the adhesiveness characteristics of the final product. Additionally, resilience values decreased with the increase of BCC concentration in the sample formulation. Volatile composition of the samples was influenced from nitrite and BCC levels in the sucuk samples and majority of the volatile compounds were terpenes. Increase of BCC concentration affected the exterior and interior a* values of the samples. All the sucuk samples had considerably acceptable sensory properties. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sucuk; Black carrot concentrate; Bioactivity; Texture; Aroma; REPLACING BEEF FAT; QUALITY CHARACTERISTICS; STAPHYLOCOCCUS-XYLOSUS; ANTIOXIDANT ACTIVITY; OXIDATIVE STABILITY; STYLE SAUSAGE; GOAT MEAT; OLIVE OIL; COLOR; NITRITE; Food Science & Technology